Characterization of Acid-Extracted Pectin-Enriched Products Obtained from Red Beet ( Beta vulgaris L. var. conditiva ) and Butternut ( Cucurbita moschata Duch ex Poiret) - Fissore, Eliana Noemi (2010)
Chemical and rheological characteristics of fractions enriched in soluble dietary fiber are reported. These fractions were obtained through acid hydrolysis of butternut (Cucurbita moschata Duch ex Poiret) and red beet (Beta vulgaris L. var. conditiva) cell wall enriched powders. Hydrolysis was performed using citric acid at different pH values and reaction times (2 and 3 h). Yields obtained for butternut fractions were between 21 and 28 g/100 g; for red beet, yields were 24 and 31 g/100 g for pH 1.5 and 11 and 17 g/100 g for pH 2.0 for previously mentioned times; in general, the increase of the yield was directly correlated with the decrease of pH and the increase of reaction time. Products enriched in low methoxyl pectins were obtained in all cases. At the lowest pH assayed, pectins were essentially constituted by homogalacturonan; a significant content of neutral sugars was determined at the higher extraction pH. Neutral sugars were constituted mainly by arabinose, galactose, rhamnose, and glucose in different proportions for each fraction; in general, butternut fractions showed high glucose contents. Flow behavior for 2.00% (w/v) aqueous systems of the different products was evaluated. Data obtained for fractions isolated at pH 1.5 fit to Herschel-Bulkley and Cross models while those isolated at pH 2.0 fit to Ostwald and Cross models. All samples showed low viscosity and, hence, poor thickening properties.